Tinjauan Hukum Pidana Islam terhadap Pelaksanaan Sanksi Adat dalam Tindak Pidana Eksploitasi Peracunan Ikan (Studi Kasus Nagari Koto Rajo Kecamatan Rao Utara Kabupaten Pasaman) - Heru Akbar; Hendri Hendri (Lembaga Yasin AlSys, 2026)
The criminal act of environmental exploitation through fish poisoning in the Aia Rasik River, Nagari Koto Rajo, Rao Utara Subdistrict, Pasaman Regency, has caused ecological damage and social unrest within the community. In this context, the implementation of customary sanctions has become one of the settlement mechanisms used by the local community. This study aims to determine the process of implementing customary sanctions against perpetrators of fish-poisoning exploitation and to analyze its conformity from the perspective of Islamic criminal law. This study employed field research using an empirical juridical approach and a qualitative research type. Data were collected through interviews, observation, and documentation involving customary leaders and the community in Nagari Koto Rajo, and were then analyzed descriptively-analytically based on the perspective of Islamic criminal law. The results showed that the implementation of customary sanctions began with community reports regarding fish deaths caused by the use of poison in the river. After an investigation was conducted by community leaders, the perpetrator was secured and subsequently deliberated upon by the Niniak Mamak, Datuak, and nagari leaders to determine the appropriate sanction. Based on the results of the deliberation, the perpetrator was subjected to a customary sanction in the form of expulsion from Nagari Koto Rajo as punishment for the act committed. The sanction was considered capable of creating a deterrent effect and preventing the recurrence of similar incidents. From the perspective of Islamic criminal law, the implementation of the customary sanction does not contradict the principles of sharia because it is oriented toward public benefit and the prevention of environmental damage. Thus, the customary sanction can be regarded as a form of ta’zir punishment aimed at safeguarding public benefit, particularly in protecting property, life, and environmental sustainability. The implication of this study emphasizes that customary sanctions can function as an effective settlement mechanism in customary communities while also strengthening the study of Islamic criminal law and the role of customary law in handling criminal acts in society.